AbaComplex Enhances Mitochondrial Biogenesis and Adipose Tissue Browning: Implications for Obesity and Glucose Regulation - Serena Sagliocchi; Elisabetta Schiano; Lucia Acampora; Fortuna Iannuzzo; Annunziata Gaetana Cicatiello; Caterina Miro; Annarita Nappi; Federica Restolfer; Mariano Stornaiuolo; Stefano Zarrilli; Fabrizia Guerra; Gian Carlo Tenore; et al. (Foods)
Adipose tissue, particularly white adipose tissue (WAT), plays a central role in energy storage and metabolic regulation. Excess WAT, especially visceral fat, is strongly linked to metabolic disorders such as obesity and type 2 diabetes. The browning of WAT, whereby white fat cells acquire characteristics of brown adipose tissue (BAT) with enhanced thermogenic capacity, represents a promising strategy to enhance metabolic health. In this study, we investigated the effects of chronic supplementation with an infusion based on lyophilized, thin nectarines rich in abscisic acid (ABA), named AbaComplex, on promoting browning of WAT and activating BAT in mice. Over 30 days, C57BL/6 mice were treated with the ABA-rich infusion, and various metabolic and molecular parameters were assessed. The results showed that the AbaComplex significantly increased the expression of browning markers, such as UCP1 and PGC1-α, in both visceral and subcutaneous WAT. Additionally, mitochondrial biogenesis and function were enhanced, evidenced by elevated mitochondrial DNA content and activity. The treatment also reduced the weight of WAT (both visceral and subcutaneous) and BAT and significantly improved glucose uptake in WAT via upregulation of GLUT4, suggesting enhanced insulin sensitivity. Overall, the pronounced browning effect in WAT underscores the potential of AbaComplex as a natural approach for combating obesity and improving metabolic health.